Beginning iPad Development for iPhone Developers - Nutting, Jack (Apress, 2012)
The world has changed. Since work on this book began, the iPad was released (selling three million units in the first 80 days), and the iPhone OS was renamed to iOS, which debuted as iOS 4 in the new iPhone 4 (which was preordered by 600,000 people the first day). Meanwhile, more than 11,000 apps were released for the iPad—a mix of iPad-only apps and universal apps, which can run on both the iPhone and the iPad. By any measure, the iPad is a runaway hit. It is already inspiring many creative uses far beyond the sort of ultimate media-consumption device that Apple began touting it as back in January. By the time this book goes to print and reaches your hands, Xcode 4 may be available (throwing a monkey-wrench into our careful descriptions of using Xcode and Interface Builder), Apple will have sold one or two million more iPads, and iOS 4 may even be available for iPad. Apple is keeping iPhone and iPad developers on their toes, and authors are no exception! We've kept all of this in mind while writing this book, and have worked to make a book that will stand the test of time, regardless of OS versions and release dates